PENGARUH SISTEM PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN NARKOTIKA TERHADAP RESIDIVIS DALAM TINDAK PIDANA PSIKOTROPIKA - Eko Nurharyanto (Kajian Hukum, 2017)
Psychotropic has benefits for medical care and health services but also has the side effect that is if they are misused. Misuse of psychotropic is very dangerous for the User, and the nation's society.The Indonesian government in tackling the misuse of psychotropic has established Act No. 5 of 1997 on Psychotropic Substances, focus of this act is aimed to prevent the use of psychotropic side effects that are qualified as crime is very detrimental to the individual, society and the State.This study was to determine the psychotropic case investigation process which is the duty and obligation of our police force must be based on a statutory provision which already exist. The implementation of common their investigation of abuse of authority committed by unscrupulous law enforcement officials, even in the public rumor that the police only the pursuit of targets set by the management and the suspect psychotropic feel trapped by the authorities.This study analyse the investigation process by investigators of the case to be reviewed psychotropic normative juridical and bring the issues that arise in the community, if it is true then the issue of what action should be taken against those responsible.We hope that this article is the result of research can be useful for law enforcement officials, especially the police and the community in general. Keywords: System Influence, Psychotropic, Penitentiary